Collaborative Care in NSCLC; the Role of Early Palliative Care - Howe, Marnie; Burkes, Ronald L. (Frontiers in Oncology, 2014)
The management of non-small-cell-lung-cancer (NSCLC) has evolved into a multidisciplinary team approach that traditionally has involved medical oncology, radiation oncology and thoracic surgery. However, in the era of personalized medicine the importance of molecular diagnostics requires adequate tissue for histologic subtyping and molecular testing and thus requires the engagement of other subspecialties such as pathology, respirology and interventional radiology. Unfortunately in 2014 the majority of patients presenting with NSCLC will succumb to their disease and the early integration of palliative care into the treatment strategy will improve the quality of life (QoL) and end of life (EOL) care of our patients and may in fact improve their overall survival.